Relapse of acute lymphoblastic leukemia presenting with ovarian torsion: A rare case report - Saket Patwardhan; Vasundhara Patil; Akshay Baheti; Shreya Shukla; Sajid Qureshi (Elsevier, 2022)
Introduction: Ovarian torsion is an emergency condition caused by complete or partial rotation of the ovarian vascular pedicle. It may be associated with underlying pathology. In a child with known leukemia who presents with ovarian torsion, relapse of disease in the form of leukemic infiltration of the ovary predisposing to torsion is an important differential diagnosis to be considered. Ultrasound is the modality of choice for imaging. MRI is used as a problem-solving tool in ambiguous cases. A prompt diagnosis is of utmost importance to enable surgical salvage and retain the function of the ovaries. Case: An 8-year-old girl child, known case of leukemia in remission presented to the emergency medical services with right iliac fossa and lower abdominal pain. On examination a firm lump was felt in the right iliac fossa. Tumor marker levels (AFP and B HCG) were within normal limits. On ultrasound, the right ovary was enlarged. Follicles were small and displaced to the periphery. On Colour Doppler, however arterial and venous flow were present in the ovary. MRI was performed which demonstrated an enlarged right ovary with peripheral small follicles. She underwent oophorectomy. The final diagnosis was right ovarian relapse of leukemia presenting with torsion. Conclusion: The radiological diagnosis in this case was an ovarian torsion. Ovary as a site of leukemic relapse, though rare, should be considered when enlarged ovary is seen in leukemic patients on remission, and torsion should be considered if there is corresponding clinical history of pain and tenderness. This case highlights the importance of keeping in mind that the ovary can be a rare site of relapse of disease and present acutely as torsion.